Pola Asuh Otoriter tidak Berhubungan Signifikan dengan Konsep Diri Siswa SMA - Santa Yopita Kemit; Lobby Loekmono; Setyorini Setyorini (Indonesian Journal of Educational Counseling, 2019)
AUTHORITARIAN PARENTING IS NOT SIGNIFICANTLY RELATED TO THE SELF-CONCEPT OF HIGH SCHOOL STUDENTS. This study aims to determine the significant relationship between authoritarian parenting and the self-concept of SMA Kristen 1 Salatiga especially students ini class XII. The measuring instrument used in this study is Scale of Parenting Style compiled by Gafoor and Kurukkan (2014) referring to the theory of Baumrind (1991) and Self-Description Questionnaire II (SDQ-II) compiled by Herbert W. Marsh (1990). The data analysis technique used in this study is Pearson Product Moment Correlation by using SPSS for Windows 20. From the results of the data analysis, the results show that there is no significant relationship between the authoritarian parenting style with the self-concept of Christian XII grade students 1 Salatiga with the correlation of rxy = 0.110 with P = 0.388> 0.05. That is, the increase or decrease in the score of the authoritarian parenting variable and the self-concept variable score cannot be determined.